The evolutionary history of sedges (Cyperaceae) in Madagascar. (6th January 2021) - Larridon, Isabel; Spalink, Daniel; Jiménez‐Mejías, Pedro; Márquez‐Corro, José Ignacio; Martín‐Bravo, Santiago; Muasya, Muthama; Escudero, Marcial
Abstract: Aim: Madagascar is renowned for its unparalleled biodiversity and endemism. With many ecosystems under threat, research is urgently needed on its unique plant diversity. This applies both to Madagascar's forests and treeless vegetation types. Sedges (Cyperaceae) are among the top 10 species‐richest angiosperm families in Madagascar (310 native species, 38% endemic), of which two‐thirds occur in open habitats. We aimed to infer the evolutionary history of sedges in Madagascar, by estimating the number, age and origins of endemic lineages, and how they diversified on the island. We tested contrasting hypotheses of (a) few colonizations but important in situ radiations against (b) a high number of anagenetic colonizations. Location: Madagascar and the surrounding Indian Ocean islands, integrated within a global dataset. Taxon: Sedge family Cyperaceae. Methods: We estimated time‐calibrated molecular phylogenies encompassing a large proportion of Madagascar's known sedge flora (incl. 55% of native species), integrating sequence data for 1, 382 accessions representing almost 25% of the c. 5, 600 sedge species worldwide, combined with ancestral area reconstruction, diversification analyses and Bayesian stochastic mapping. Results: Cyperaceae lineages arrived in Madagascar from c. 40 Mya with many arriving more recently. About 20 endemic lineages of Cyperaceae occur on the island, of which only six encompass more than five species. All except one of the endemic lineages that diversified in Madagascar use the C3 photosynthetic pathway. The main biogeographical links of Madagascar's sedge flora are to Southern and Tropical Africa. Main conclusions: The biogeographical history of Cyperaceae in Madagascar is a chronicle of relatively recent multiple in and out processes of long‐distance dispersal colonizations constrained by distance. Also, the Madagascar region is not only a 'sink' for immigrant taxa, in situ diversification and dispersal to other regions also occurred. Some of the most diverse endemic lineages show clear adaptation to local environments.